Ecological Consequences of Climate Change on Pioneer Business - Abbas, Mazhar; Shabbir, Muhammad Salman; Mir, Nimer Qayum; Bibi, Asia; Siddiqi, Ahmed F. (Revista de la Universidad del Zulia, 2020)
Climate change is impacting business matters with a wide range of ramifications including ecological, political, social and economic. It is evident that certain sectors, companies, industries and regions are prone to climate-related risks more than others in the same field. It presents itself a central challenge to business enterprises. This study derives different methods to address the World’s biggest challenges. For this purpose, DuPont organization engaged in R & D, new innovations, youth educational programs, rural communities’ development. Other than that management approaches are reducing the foot prints, escalating the innovation process of company to develop the advanced agriculture and nutritional products and this will be possible only through sustainable innovation process and providing the transparency & engagement to its society and shareholders. This study tries to described that how the Ecological Consequences of climate changes effect the business methods and research methods of the company. Furthermore, our paper contributes to the literature on business and the natural environment by identifying how the climatic changes force the organization to take different decisions?